As concepções dos(as) professores(as) de Dois Vizinhos sobre a temática da sexualidade em sala de aula - Souza, Andréia de (2023)
This research sought to understand the conception of teachers at state schools in the municipality of Dois Vizinhos in southwestern Paraná; starting from the reading and analysis of some research correlated with the theme highlighted here, as well as the analysis of some documents that regulate school curricula and the application of questionnaires to understand what teachers report about the development of the theme of sexuality in the classroom . To this end, we carried out bibliographical, documentary, descriptive and field research of a qualitative and quantitative nature based on Marxist theory, taking as a starting point for the theoretical – methodological reference historical – dialectical materialism, in order to analyze the contradictions, possibilities and limitations of sexuality in the classroom. Since the central problem of this research was to investigate, what was the conception of teachers, of science teaching, of the eighth years of state schools in the municipality of Dois Vizinhos in the Southwest of Paraná when needing to work on issues aimed at student's sexuality and what has this scenario been like after the political period of 2018? and to analyze this problem, we defined three specific objectives, which were to understand and historically contextualize sexuality, analyze how sexuality appears in school documents (BNCC, PCNs, PPPs and textbook) and identify the teachers' conception( as) participants in the research on sexuality being worked on in the classroom context, through the answers obtained by the questionnaire applied. Our social justification was to understand sexuality in a broad way, as well as pointing out the importance of the topic being discussed in the classroom, as possibilities for reflection, dialogue and knowledge for teachers, students and society in general. Thus anchored in bibliographical research, we see the great importance of talking about sexuality in the classroom, especially during adolescence, a period of many discoveries. However, when we verify in documentary research the succinct way in which sexuality appears in the documents used by the school for its curricular basis, we believe that these documents do not come close to being able to cover everything that involves sexuality. But we also realize that, even in the midst of so many challenges, when it comes to sexuality, there are many teachers and institutions that are concerned with treating it in its entirety and not in a fragmented way.